2019
DOI: 10.1177/1724600819831404
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum high-density lipoprotein cholesterol as a predictor of poor survival in patients with clear cell renal cell cancer

Abstract: Purpose: Numerous studies have suggested that dyslipidemia is closely related to various cancers and the high-density lipoprotein cholesterol (HDL-C) levels are associated with the outcome of cancer patients. However, the predictive value of HDL-C in patients with renal cell carcinoma remains unclear. Our study aims to explore the relationship between the levels of serum HDL-C and the prognosis of renal cell carcinoma. Methods: A total of 308 patients diagnosed with clear cell renal cell carcinoma (CCRCC) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Many studies have shown that preoperative cholesterol levels in cancer patients can influence postoperative prognosis, and cholesterol level has been used to construct a model to predict patient survival [11][12][13][14]. Cholesterol accumulation is a common feature of cancer tissue, and recent studies have shown that it plays an important role in breast, bladder, colorectal, and other cancers [15]. The mechanism of cholesterol metabolism in cells has been largely understood through current studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that preoperative cholesterol levels in cancer patients can influence postoperative prognosis, and cholesterol level has been used to construct a model to predict patient survival [11][12][13][14]. Cholesterol accumulation is a common feature of cancer tissue, and recent studies have shown that it plays an important role in breast, bladder, colorectal, and other cancers [15]. The mechanism of cholesterol metabolism in cells has been largely understood through current studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many cancers lead to metabolic disorders in the body, and disorders of lipid metabolism have been reported to play a key role in the pathogenesis of cancer. Studies have found correlations between serum lipids and many types of tumors such as breast cancer and gastric cancer ( 20 ). High-density lipoprotein cholesterol, a serum lipid, has been shown to correlate with tumor incidence and mortality ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Serum TC and HDL-C levels have been reported to be associated with the prognosis in RCC patients [ 24 , 25 ]. This is the first study that demonstrated the association between preoperative LDL-C levels and the prognosis of RCC patients after nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LDL-C can promote the proliferation and migration of cancer cells [ 22 , 23 ]. Recently, high-density lipoprotein cholesterol (HDL-C) and total cholesterol (TC) have been considered independent factors for the prognosis of RCC patients [ 24 , 25 ]. However, little is known about the prognostic value of LDL-C in RCC patients.…”
Section: Introductionmentioning
confidence: 99%